2017
DOI: 10.1016/j.scienta.2016.11.049
|View full text |Cite
|
Sign up to set email alerts
|

The influence of high tunnel on yield and berry quality in three floricane raspberry cultivars

Abstract: Growing raspberries in polyethylene tunnels is becoming more and more common. We wanted to examine the effect of high tunnel growing conditions on yield and berry quality in three floricane raspberry cultivars, 'Glen Ample', 'Glen Dee', and 'Maurin Makea', under Northern high-latitude conditions. Compared to the open field, fruit yield per cane was doubled in the tunnel. Fruit bioactive properties, including phenolic compounds and antioxidant activity, were not affected by the tunnel growing conditions. Of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…However, not all vegetables or fruits showed such decreasing trend of bioactive compounds. Except for our recent study [31], Palonen et al (2017) demonstrated that high tunnel did not significantly affect the phenolic compound contents in three varieties of raspberry [34]. Hence, the effect of high tunnel cultivation on bioactive compounds in vegetables or fruits may be cultivar-and variety-dependent.…”
Section: High Tunnel Cultivationmentioning
confidence: 55%
“…However, not all vegetables or fruits showed such decreasing trend of bioactive compounds. Except for our recent study [31], Palonen et al (2017) demonstrated that high tunnel did not significantly affect the phenolic compound contents in three varieties of raspberry [34]. Hence, the effect of high tunnel cultivation on bioactive compounds in vegetables or fruits may be cultivar-and variety-dependent.…”
Section: High Tunnel Cultivationmentioning
confidence: 55%
“…Fruit length, width and weight, on the other hand, differed somewhat among the different treatments, while fruit shape (length/width ratio) and yield were not significantly affected (Table 1). The yield potential of raspberries is mainly determined by cultivar predisposition, although environmental conditions during floral initiation in the previous season also play an important role (Sønsteby et al, 2009;Palonen et al, 2017), which may be why fruit yield was not affected by treatment in our study, since all plants yielded approx. 1.1 kg fruit per plant.…”
Section: Fruit Characteristicsmentioning
confidence: 69%
“…Although genetic predisposition is the major factors influencing fruit quality (Milivojevic et al, 2011;Kula et al, 2016), different agricultural practices (Qiu et al, 2016;Palonen et al, 2017), fruit maturity (Stavang et al, 2015) and environmental conditions can also affect berry metabolite amounts and composition (Anttonen and Karjalainen, 2005;Remberg et al, 2010;Mazur et al, 2014a,b). Raspberries, like some other berries, ripen successively and are harvested over a period of a few weeks.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to minimize problems caused by climatic adversities and improve fruit quality is the growing of plants under plastic cover. This practice may modify the conformities of climatic variables, mainly light intensity and quality, air temperature and relative humidity, wind incidence and speed, and damages caused by insect pests and diseases (Palonen et al, 2017). Furthermore, plastic cover above the canopy allows to improve fruit yield and quality through the development of a favorable microclimate, which protects the plants and provides beneficial effects of climatic variations (Bradish et al, 2015;Curi et al, 2015;Palonen et al, 2017;Yao and Rosen, 2011).…”
Section: Introductionmentioning
confidence: 99%